2015
DOI: 10.1371/journal.pone.0141582
|View full text |Cite
|
Sign up to set email alerts
|

Post-Prandial Protein Handling: You Are What You Just Ate

Abstract: BackgroundProtein turnover in skeletal muscle tissue is highly responsive to nutrient intake in healthy adults.ObjectiveTo provide a comprehensive overview of post-prandial protein handling, ranging from dietary protein digestion and amino acid absorption, the uptake of dietary protein derived amino acids over the leg, the post-prandial stimulation of muscle protein synthesis rates, to the incorporation of dietary protein derived amino acids in de novo muscle protein.Design12 healthy young males ingested 20 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
115
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 56 publications
(74 reference statements)
5
115
0
1
Order By: Relevance
“…In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation (Fig. In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation (Fig. In line with previous research (Gorissen et al 2014;Groen et al 2015;Trommelen et al 2016), we showed that the dietary protein-derived amino acids are effectively being taken up and released in the systemic circulation (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This translates to 2.0 Ϯ 0.2 g of muscle protein and equals 9.9 Ϯ 1.2% of the ingested dietary protein-derived amino acids that were incorporated in de novo muscle protein. These data are in line with our recent calculations (19) and demonstrate the possibilities of using intrinsically labeled protein to demonstrate the metabolic fate of dietary protein-derived amino acid in vivo in humans (35).…”
Section: Discussionsupporting
confidence: 89%
“…13 C] phenylalanine-labeled protein allows us to assess the percentage of the ingested protein that was released into the circulation and used for de novo muscle protein synthesis (19). Based on the assumption that L-[1-…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has highlighted the direct or indirect affect that nutrition can have on the known inputs that regulate mTORC1; amino acids, glucose, and growth factors (Drummond et al, 2009). This is supported by evidence that essential amino acids have a stimulatory effect on muscle protein synthesis (Groen et al, 2015) and the observation that carbohydrate ingestion post-resistance exercise acts to reduce protein breakdown (Borsheim et al, 2004). Hence, control of nutrient intake is of the utmost importance when conducting research involving muscle remodelling as part of the recovery process.…”
Section: Discussionmentioning
confidence: 96%